Exploring the hemoglobin-to-red blood cell distribution width ratio (HRR) to peripheral arterial disease nexus: a comprehensive analysis of NHANES data from 1999 to 2004 - Yu, Zhihai; Lu, Bin; Han, Rui; Tu, Can (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to investigate the correlation between the Hemoglobin-to-Red Blood Cell Distribution Width Ratio (HRR) and Peripheral Artery Disease (PAD) prevalence, utilizing data from the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2004.MethodsThe study employed a cross-sectional design, analyzing data from 5,196 participants aged 40 and above. PAD was diagnosed using the Ankle-Brachial Index (ABI), with ABI less than 0.9 indicating PAD. HRR, calculated as the ratio of hemoglobin (HB) to red blood cell distribution width (RDW), was stratified into quartiles. Covariates included demographic and clinical variables such as BMI, lipid profiles, and diabetes status. Logistic regression analysis was conducted to assess the relationship between HRR and PAD, adjusting for potential confounders.ResultsThe study found that higher HRR quartiles were associated with a decreased risk of PAD. After adjusting for confounders, the odds ratios for PAD in relation to the second, third, and fourth quartiles of HRR compared to the first quartile were 0.71, 0.62, and 0.44, respectively (P < 0.001). A one-unit increase in HRR corresponded to a 56% reduction in the probability of PAD. ROC analysis indicated HRR as a stronger protective factor for PAD compared to other variables. Stratified analyses revealed that younger age and lower BMI amplified the protective effect of HRR on PAD.ConclusionThe study demonstrated a significant inverse relationship between HRR and PAD, suggesting that HRR may serve as a protective factor against PAD. This finding highlights the potential role of HRR in the pathogenesis of PAD and its clinical implications.